Financial Well-Being and Self-Efficacy in Sandwich Generation: The Role of Mindfulness - Yuyun Karystin Meilisa Suade; Wirawan Endro Dwi Radianto; Murpin Josua Sembiring (Yayasan Vifada Cendikia Indonesia, 2026)
Purpose: Financial Mindfulness is essential for complementing self-confidence in managing personal finances to achieve financial well-being. This study aims to investigate how individuals' self-efficacy influences their mindfulness in making prudent financial decisions, thereby attaining financial well-being. The research subjects are members of the Sandwich Generation, who face the dual financial burden of caring for aging parents and supporting children, often experiencing stress and complexity in financial management. Research Design and Methodology: This study employs a quantitative design with a sample of 281 respondents from the Sandwich Generation in Indonesia. Data were analyzed using Structural Equation Modelling - Partial Least Square (SEM-PLS) with SMARTPLS Version 3. Findings and Discussion: The findings indicate that Financial Self-Efficacy positively influences Financial Mindfulness, Financial Mindfulness positively impacts Financial Well-Being, and Financial Self-Efficacy positively affects Financial Well-Being. Additionally, Financial Mindfulness has been found to positively mediate the effect of Financial Self-Efficacy on Financial Well-Being, which is a novel contribution of this research Implications: The managerial implications of these findings are valuable for financial planners, financial institutions, and policymakers focusing on the financial well-being of the Sandwich Generation in Indonesia.